UN Human Rights Institutions and the Environment: Synergies, Challenges, Trajectories - Sumudu Atapattu (Routledge, 2023)
This book presents an in-depth analysis of how UN human rights institutions and mechanisms have addressed environmental protection, sustainable development, and climate change. Despite the increasing involvement of UN human rights bodies in addressing environmental degradation and climate change, a systematic review of the convergence between human rights and the environment in these bodies has not been carried out. Filing this lacuna, this book surveys the resolutions, general comments, concluding observations, decisions on individual communications and press releases. It identifies principles that have emerged, explores the ways in which human rights charter-based and treaty-based institutions are interpreting environmental principles and examines how they contribute to the emerging field of human rights and the environment. Given the disproportionate effect that polluting activities have on marginalized and vulnerable groups, Atapattu also discusses how these human rights mechanisms have addressed the impact on women, children, indigenous peoples, people with disabilities, and racial minorities. Written by a world-renowned expert on human rights and the environment, this book will be of great interest to students and scholars researching and teaching in this important field of study.
Keywords: 320; climate change; environmental degradation; environmental principles; human rights; sustainable development